Photosynthesis-ecophysiological properties of beech (Fagus sylvatica L.) under the exclusion of ambient UV-B radiation - Láposi, Réka (Acta Biologica Szegediensis, 2002)
The effects of exclusion of UV-B radiation on leaf physiology of beech seedlings regenerating in a deforested area were studied in field. Under UV-B exclusion the chlorophyll content of leaves was higher, the chlorophyll a/b ratio and the carotenoid content was lower than in leaves under the ambient level of UV-B radiation. In leaves developed under the exclusion of UV-B a smaller degree of conversion of violaxantin to zeaxantin and atheraxantin was found at noon. The results showed that the ambient level of UV-B radiation decreased the maximum photochemical efficiency (FyFJ of the dark-adapted leaves, especially at noon. Beech leaves contained significantly higher quantities of UV-B absorbing compounds on the basis of leaf area at the ambient UV-B than under the UV-B exclusion. Flavonoid accumulation took place in close correlation with the increase of specific leaf weight as compared to the leaves developed under UV-B exclusion.